Pastel workbook : a complete course in ten lessons - Simmonds, Jackie (Devon, Eng. : David & Charles, 1999)
Ten easy-to-follow lessons demonstrate the basic techniques used when working with pastels.
Includes index.
Library Journal.
Adult
Keywords: Pastel drawing -- Technique; Pastel drawing -- Technique